The Effect of Quality Product, Price Perception, and Promotion onVivo Smartphone Purchase Decisions: A Study at the Archa PhoneCounter in Bekasi - Melyani, Melyani; Swastika, Rahayu; Widyastuti, Reni; Shaura, Rizkiana Karmelia; Pramularso, Eigis Yani; Anggarini, Desy Tri; Tambunan, Diana (Journal of Management and Informatics, 2025)
This study investigates the influence of product quality, price perception, and promotion on Vivosmartphone purchase decisions. A quantitative survey was administered to 100 consumers at the ArchaPhone Counter in Bekasi using purposive sampling. Multiple linear regression analysis revealed thatall three variables have a significant positive partial effect on the purchase decision. The modelexplained 85% of the variance (Adjusted R² = 0.726), confirming their simultaneous influence. Productquality was identified as the most dominant predictive factor, validating its critical role in consumerchoice.